Analisis Peran Badan Permusyawaratan Desa Dalam Pengawasan Pembangunan Infrastruktur Publik Pada Pembangunan Rest Area Desa Margoyoso Kecamatan Salaman Kabupaten Magelang - Nafal Nafal Farhand Rachmad; Indah Kusuma Dewi Indah Kusuma Dewi; Sapardiyono Sapardiyono (Perkumpulan Maju Karya Yogyakarta, 2025)
AbstracThis research aims to analyze the role of the Village Consultative Body (Badan Permusyawaratan Desa/BPD) in supervising the development of public infrastructure in the Rest Area construction project in Margoyoso Village, Salaman District, Magelang Regency. As an institution representing the village community, the BPD has key functions that include drafting and approving village regulations, accommodating community aspirations, and overseeing the implementation of development carried out by the village government.In the context of the rest area construction, the supervisory function of the BPD becomes crucial to ensure the proper use of funds, the quality of work, and the implementation of the program in accordance with the village development plan. This study employs a qualitative descriptive method, with data collected through interviews, direct observation, and document analysis. The findings indicate that the BPD has carried out its supervisory role; however, several challenges remain, such as limited technical understanding related to infrastructure development, suboptimal coordination between the BPD and the village government, and low community participation in the evaluation process. Nevertheless, the supervision conducted by the BPD has contributed to improving transparency and accountability in the implementation of the rest area development.This research recommends enhancing the capacity of BPD members through training, strengthening communication mechanisms with the village government, and increasing community involvement to create effective and sustainable development oversight.